2017
DOI: 10.1186/s40425-017-0275-9
|View full text |Cite|
|
Sign up to set email alerts
|

Genetic engineering of human NK cells to express CXCR2 improves migration to renal cell carcinoma

Abstract: BackgroundAdoptive natural killer (NK) cell transfer is being increasingly used as cancer treatment. However, clinical responses have so far been limited to patients with hematological malignancies. A potential limiting factor in patients with solid tumors is defective homing of the infused NK cells to the tumor site. Chemokines regulate the migration of leukocytes expressing corresponding chemokine receptors. Various solid tumors, including renal cell carcinoma (RCC), readily secrete ligands for the chemokine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
110
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 125 publications
(124 citation statements)
references
References 45 publications
3
110
0
Order By: Relevance
“…Previous studies have shown that the enhanced expression of either chemokines or chemokine receptors can promote the tumor-specific migration of human cytotoxic cells. 19 31 46 47 For NK cells, the enforced expression of specific chemokine receptors can improve their accumulation with tumors. 19 Consistent with this, we showed that CCR5 overexpression enhances the directional movement of NK cells (figures 1 and 2).…”
Section: Open Accessmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have shown that the enhanced expression of either chemokines or chemokine receptors can promote the tumor-specific migration of human cytotoxic cells. 19 31 46 47 For NK cells, the enforced expression of specific chemokine receptors can improve their accumulation with tumors. 19 Consistent with this, we showed that CCR5 overexpression enhances the directional movement of NK cells (figures 1 and 2).…”
Section: Open Accessmentioning
confidence: 99%
“…Lentiviruses are a powerful tool for gene modification in NK cells, 19 using which we can construct CCR5-overexpressing NK Open access cells. Additionally, oncolytic viruses (OVs) represent an attractive tool for local adaption of the tumor microenvironment as they can selectively replicate and produce exogenous proteins within tumor cells.…”
Section: Introductionmentioning
confidence: 99%
“…[47][48][49][50][51] The importance of migration and homing of NK cells to disease sites is critical to its success for cell-based immunotherapy upon adoptive infusion. 52 This indicates that CXCR2 represents a potential chemokine receptor that can be overexpressed on NK cells for improving infiltration into tumours. Intra-tumoural infiltration of one NK cell subpopulation in tumours of renal cell carcinoma patients correlates with high concentrations of CXCR2 ligands.…”
Section: Improving Nk Cell Infiltrationmentioning
confidence: 99%
“…Intra-tumoural infiltration of one NK cell subpopulation in tumours of renal cell carcinoma patients correlates with high concentrations of CXCR2 ligands. 52 Genetic engineering of human NK cells to express CXCR2 has been shown to improve their ability to specifically migrate along a chemokine gradient of recombinant CXCR2 ligands in vitro, as well as migration to renal cell carcinoma in the mouse model. 52 This indicates that CXCR2 represents a potential chemokine receptor that can be overexpressed on NK cells for improving infiltration into tumours.…”
Section: Improving Nk Cell Infiltrationmentioning
confidence: 99%
See 1 more Smart Citation